2012
DOI: 10.1021/ol303109m
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Mediated Intramolecular Electrophilic Aromatic Cyclization in Allylamines: A General Route to Synthesis of Quinolines, Pyrazolo[4,3-b]pyridines, and Thieno[3,2-b]pyridines

Abstract: An unprecedented synthesis of aromatic ring annulated pyridines from suitably substituted primary allylamines via intramolecular electrophilic aromatic cyclization mediated by molecular iodine under mild conditions is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 46 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…[10] In one of our research programs focused on realizing the synthetic potential of MBH chemistry,w ed eveloped synthesis of quinolines,p yrazolo [4,3-b]pyridines,a nd thieno[3,2-b]pyridines by I 2 -mediated intramolecular electrophilic aromatic cyclization of primary allylamines. [11] Later,Y ue tal. accomplished the synthesis of quinolones from allyl azides by cyclization of iminyl radicals generated by N-bromosuccinimide in light.…”
mentioning
confidence: 98%
“…[10] In one of our research programs focused on realizing the synthetic potential of MBH chemistry,w ed eveloped synthesis of quinolines,p yrazolo [4,3-b]pyridines,a nd thieno[3,2-b]pyridines by I 2 -mediated intramolecular electrophilic aromatic cyclization of primary allylamines. [11] Later,Y ue tal. accomplished the synthesis of quinolones from allyl azides by cyclization of iminyl radicals generated by N-bromosuccinimide in light.…”
mentioning
confidence: 98%
“…However, the methoxy group substituted substrates gave relatively low yields ( 3b and 3e ; 3c and 3f ), whereas increasing the catalyst loading led to inferior yields. The reason for this phenomenon is unclear, we think that the electronic properties and the coordination abilities of these substrates should be responsible for the observed results . In addition, 1‐naphthyl and 2‐naphthyl substituted acroleins 1m and 1n can also be applied to this reaction, providing a facile method to access benzene‐fused indene type of tricycles ( 3m–n) , which are also useful carbocyclic skeletons .…”
Section: Resultsmentioning
confidence: 67%
“…Based on the above results and previous works, a tentative reaction pathway is described in Scheme . Initially, AlCl 3 ‐catalyzed condensation of the aldehyde 1a (or 1o ) and TsNH 2 leads to the formation of resonance‐stabilized iminium ion A (or C ), A can isomerize to its Z isomer B .…”
Section: Resultsmentioning
confidence: 99%
“…The best yield of 2 a (55 %) was obtained in dioxane, whereas, 3 a was major product with 45 % yield in water. Yield of 2 a increased slightly on increasing the reaction temperature to 100 8C but decreased significantly on decreasing the reaction temperature to 60 8C ( Table 1, entry [14][15]. This variation in yield of 2 a and 3 a with change in temperature indicated that 2 a is formed in major amount at higher temperature, whereas 3 a is formed in major amount at lower temperature.…”
Section: Resultsmentioning
confidence: 96%